Infra Red Spectra of Different Species of Cultivated Oyster Mushrooms Possible Tool for Identifying Bioactive Compounds and Establishing Taxonomic Linkage - Das, Bodhaditya; Rajkonwar, Jadab; Jagannath, A.; Raul, Prasanta Kumar; Deb, Utsab (Defence Life Science Journal, 2020)
Mushrooms are macrofungi that serve as a vegetarian source of protein along with various bio-active molecules of primary health importance. The activity of the bio-active molecules range from antioxidant, immunomodulation, hepatoprotection. Cultivated oyster mushrooms are also rich in these components which may be estimated quantitatively by skill intensive ‘destructive’ chemical techniques. Infra Red spectroscopy provides a non-destructive user friendly technique to quickly assess the presence of bio-active compounds in mushroom species to be used as a quality control measure as this non-destructive tool can be used to segregate mushroom harvest according to availability of bioactive compounds. IR spectra based strain classification and taxa delimitation of mushroom samples are also attempted vis a vis DNA sequence based phylogeny analysis of the same, but no correlation is observed between the two types of phylogeny analysis.